2022
DOI: 10.1097/pec.0000000000002620
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Prehospital Protocols for Pediatric Respiratory Distress Management in the United States

Abstract: Objective: This study aimed to compare statewide emergency medical services protocols for the management of pediatric respiratory distress. Methods:We performed a descriptive study of emergency medical services protocols for the management of pediatric respiratory distress in the United States, excluding those without model or mandatory protocols. We compared medication recommendations for specific disease processes, including asthma, croup, epiglottitis, anaphylaxis, generalized respiratory distress, intubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Administration by the oral route may overcome this burden, though many EMS protocols do not allow for the use of oral corticosteroids. 26 In a pilot study, a change in prehospital protocols to include oral corticosteroid administration was associated with a decrease in hospital admission rate and LOS. 13 When systemic corticosteroids can only be administered intravenously, it may be prudent to avoid the time spent securing IV access to administer systemic corticosteroids in EMS encounters that are anticipated to be shorter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration by the oral route may overcome this burden, though many EMS protocols do not allow for the use of oral corticosteroids. 26 In a pilot study, a change in prehospital protocols to include oral corticosteroid administration was associated with a decrease in hospital admission rate and LOS. 13 When systemic corticosteroids can only be administered intravenously, it may be prudent to avoid the time spent securing IV access to administer systemic corticosteroids in EMS encounters that are anticipated to be shorter.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that systemic corticosteroids are most commonly available and administered by the IV route, difficulty in obtaining IV access represents a unique challenge in the administration of systemic corticosteroids to children. Administration by the oral route may overcome this burden, though many EMS protocols do not allow for the use of oral corticosteroids 26 . In a pilot study, a change in prehospital protocols to include oral corticosteroid administration was associated with a decrease in hospital admission rate and LOS 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Those low rates are further supported by a Florida statewide study 11 and a national study, 12 which reported systemic corticosteroid administration rates to children of 11% and 8%, respectively. One potential reason for those low rates is that IV methylprednisolone is the most commonly used systemic corticosteroid in EMS protocols, 13,14 yet there are numerous barriers to prehospital pediatric IV placement resulting in a minority of pediatric EMS patients receiving prehospital IVs from EMS clinicians. 15,16 Therefore, there is a need to study both oral and IV systemic corticosteroid options for EMS administration to pediatric asthma patients.…”
Section: Introductionmentioning
confidence: 99%